2022
DOI: 10.3892/ijo.2022.5387
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory antitumor effect of interferon‑beta combined with gemcitabine in pancreatic cancer

Abstract: Resistance to gemcitabine is common and critically limits its therapeutic efficacy in patients with pancreatic cancer. Interferon-beta (IFN-β) induces numerous antitumor effects and synergizes with gemcitabine treatment. The immunomodulatory effects of this treatment regimen have not yet been described. In the present study, the antitumor effect of IFN-β combined with gemcitabine was investigated in immune competent mice. Mouse KPC3 cells were used in all experiments. Treatment effects were determined with cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Yoshimura et al [ 110 ] reported that INF-β increased the anticancer effect in combined therapy with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) compared to TRAIL monotherapy. Blaauboer et al [ 111 ] showed that combining gemcitabine therapy with INF-β gives better results in vitro than monotherapy. However, INF-β loses its ability to promote the immunologic response of the cells after combining with gemcitabine.…”
Section: Transgenes Enhancing Efficiencymentioning
confidence: 99%
“…Yoshimura et al [ 110 ] reported that INF-β increased the anticancer effect in combined therapy with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) compared to TRAIL monotherapy. Blaauboer et al [ 111 ] showed that combining gemcitabine therapy with INF-β gives better results in vitro than monotherapy. However, INF-β loses its ability to promote the immunologic response of the cells after combining with gemcitabine.…”
Section: Transgenes Enhancing Efficiencymentioning
confidence: 99%
“…In addition, IFN-alpha2 has also demonstrated a potent stem-cell-targeting potential by reactivating dormant JAK2V617F-positive stem cells and put them in cycle to be killed directly by IFN-alpha2 and IFN-activated immune cells (e.g., dendritic cells, NK-cells, T-cells) [240,241,244]. Interferon-beta (IFN-beta) has similar beneficial anti-cancer effects but is likely much stronger than IFN-alpha2, making it a potential alternative to IFN-alpha in the treatment of MPNs [452] and possibly also in the treatment of other cancers as well in combination with novel immunotherapies [453][454][455][456][457][458][459][460][461][462]. Remarkably, IFN-beta has been shown to suppress cancer stem cell properties in triple-negative breast cancer [460,461].…”
Section: Statins and Metforminmentioning
confidence: 99%